Tykompartmentna mathematical model mass transfer between liquid sector during the human hemodialysis - Поліщук, С.Т. (Proceedings of National Aviation University (archive), 2006)
The mathematical model of patient’s organism as control object in hemodialysis system is proposed. The necessity of structural changes in control system of extracorporeal replacement kidney function is proved.